Bivalirudin versus heparin in adult and pediatric patients with extracorporeal membrane oxygenation therapy: A systematic review and meta-analysis - Liyao Liu; Feng Liu; Jixiang Tan; Lin Zhao (Elsevier, 2022)
Background: Our study sought to investigate the efficacy and safety of bivalirudin versus those of unfractionated heparin (UFH) in patients undergoing extracorporeal membrane oxygenation (ECMO). Methods: PubMed, EMBASE and Cochrane Library were searched for studies enrolling ECMO patients on bivalirudin and UFH (from inception till July 2021). Meta-analysis was conducted. The I2 statistic and p value were used in measuring heterogeneity, and random effects or fixed-effect model was adopted. The Newcastle-Ottawa Scale was used for the risk of bias assessment. Sensitivity and subgroup analyses were undertaken. We performed Egger's test to evaluate publication bias. Results: Fourteen eligible retrospective observational studies with 1501 subjects were identified. Compared with UFH, bivalirudin significantly reduced the risk of in-circuit thrombosis (OR = 0.44, 95% CI [0.31-0.61], p = 0.000), thrombosis (OR = 0.61, 95% CI [0.45-0.83], p= 0.002) and hospital mortality (OR = 0.78, 95% CI [0.61-0.99], p = 0.04) and had a positive impact on survival ECMO (OR = 1.50, 95% CI [1.04-2.16], p= 0.032). Decrease in risk of bleeding (OR = 0.36, 95% CI [0.14-0.91], p = 0.031) associated with bivalirudin was observed. Sources of heterogeneity were identified, and sensitivity analysis revealed similar results. Conclusion: Our meta-analysis suggested that bivalirudin was associated with the decreased risk of in-circuit thrombosis, thrombosis, hospital mortality and bleeding in patients on ECMO and improved survival ECMO, indicating the superiority of bivalirudin to UFH in terms of efficacy and safety.